2009
DOI: 10.1523/jneurosci.4184-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Brain Fiber Architecture and Intellectual Performance

Abstract: The study is the first to analyze genetic and environmental factors that affect brain fiber architecture and its genetic linkage with cognitive function. We assessed white matter integrity voxelwise using diffusion tensor imaging at high magnetic field (4 Tesla), in 92 identical and fraternal twins. White matter integrity, quantified using fractional anisotropy (FA), was used to fit structural equation models (SEM) at each point in the brain, generating three-dimensional maps of heritability. We visualized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
278
5
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(307 citation statements)
references
References 75 publications
19
278
5
5
Order By: Relevance
“…It has been demonstrated that DTI measures reflect heritable components of brain structure (Chiang et al, 2009;Kochunov et al, 2010), and are useful to delineate potential fiber tracts anomalies related to psychiatric genetic risk variants. Specifically, genetic associations of risk variants for mood disorders with FA in frontolimbic tracts relevant for emotion processing have been repeatedly described (Alexopoulos et al, 2009;Pacheco et al, 2009), as well as associations of schizophrenia risk variants linked to altered neurodevelopment with FA in prefrontal cognitive pathways (McIntosh et al, 2008;Zuliani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that DTI measures reflect heritable components of brain structure (Chiang et al, 2009;Kochunov et al, 2010), and are useful to delineate potential fiber tracts anomalies related to psychiatric genetic risk variants. Specifically, genetic associations of risk variants for mood disorders with FA in frontolimbic tracts relevant for emotion processing have been repeatedly described (Alexopoulos et al, 2009;Pacheco et al, 2009), as well as associations of schizophrenia risk variants linked to altered neurodevelopment with FA in prefrontal cognitive pathways (McIntosh et al, 2008;Zuliani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, and analogous to clinical and molecular genetics studies, independent replication is important to gain confidence in the validity of reported findings. In order to minimize spurious associations, we used an ethnically homogenous sample and outcome measures such as FA and radial diffusivity (RD) that are known to be heritable (Chiang et al, 2009;Kochunov et al, 2010). We also attempted to apply rigorous methodology during diffusion imaging acquisition and processing by using a cardiac gated sequence, acquiring isotropic voxels (Smith et al, 2007), excluding data affected by motion, correcting for image distortions caused by magnetic susceptibility (Embleton et al, 2010) and using methods to enhance accuracy of normalization in group analyses (Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have combined structural and functional data (Choi et al, 2008), structural and functional networks (Li et al, 2009;van den Heuvel, Stam, Kahn, & Hulshoff Pol, 2009), and genetic modeling (Chiang et al, 2009). These approaches show that the synthesis of different techniques may be necessary to get a handle on the nature of g and the brain.…”
mentioning
confidence: 99%
“…Measures of white matter integrity derived from DTI, such as fractional anisotropy (FA), are highly heritable (Lee et al, 2008;Chiang et al, 2009;Kochunov et al, 2010;Lee et al, 2010;Patel et al, 2010;Chiang et al, 2011b). As such, they may be useful as intermediate measures or 'endophenotypes' (Meyer-Lindenberg and Weinberger, 2006;de Geus et al, 2008;Hall and Smoller, 2010;Marenco and Radulescu, 2010) for assessing genetic influences on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that this would help predict brain integrity, as measured by DTI-derived FA, more powerfully than a single-locus genetic test. We focus on the corpus callosum, as it is the largest white matter structure in the brain, easy to examine at the brain's midline, highly heritable (Chiang et al, 2009;Brouwer et al, 2010;Kochunov et al, 2010), and well studied in neurology and psychiatry as the primary commissure connecting the two brain hemispheres (Foong et al, 2000;Alexander et al, 2007). We chose FA as the DTI measure of white matter structure, as it has been shown to have higher heritability than other DTI parameters, such as radial and axial diffusivity (Kochunov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%